A Digital Twin based Service Oriented Application for a 4.0 Knowledge Navigation in the Smart Factory. Issue 11 (2018) - Padovano, Antonio; Longo, Francesco; Nicoletti, Letizia; Mirabelli, Giovanni
Abstract: This research illustrates how a 'Knowledge as a Service' approach endows a 3.0 digitalized factory to become a 4.0 Smart Factory. An application prototype based on a Digital Twin as Service Provider for a 4.0 knowledge fruition has been designed and developed to enable operators facing the highly dynamic factory floor and to have their 'virtual eyes and hands' on the physical system. The application has been deployed in a real factory floor and test results show its potential benefits on the industrial performances in terms of productivity (cycle and setup times) and of process quality standards (production waste rate).